Species distribution and epidemiological characteristics of superficial fungal infections in Southeastern Serbia. Issue 5 (14th March 2019) - Otašević, Suzana; Momčilović, Stefan; Golubović, Milan; Ignjatović, Aleksandra; Rančić, Nataša; Đorđević, Marina; Ranđelović, Marina; Hay, Roderick; Arsić‐Arsenijević, Valentina
Summary: Background: Superficial fungal infections (SFI), one of the most prevalent diseases in the world, are infections of keratin‐rich structures of human body mostly caused by dermatophytes and yeasts. Objectives: The goal of this study was to determine the possible changes in the epidemiology of SFI on the territory of Southeastern Serbia and to investigate epidemiological characteristics and the influence of SFI on the patient's quality of life. Methods: From 2012 to the end of 2017, samples of 1643 patients (568 males and 1075 females, mean age 40.32 ± 22.44 years) with suspected SFI from Southeastern Serbia were examined using the standard mycological methods. The questionnaires were used to investigate epidemiological characteristics. Results: Superficial fungal infections were diagnosed in 20.5% (n = 336) of patients. In the group of dermatophytes, the most prevalent was Microsporum canis (63.9%, n = 76) followed by Trichophyton mentagrophytes (21.8%, n = 26). Non‐ albicans Candida species were dominant aetiological agents of superficial candidosis (62.3%). BMI ≥25 kg/m 2 ( P = 0.019) was determined as an independent risk factor for SFI. There was a statistically significant difference in the EQVAS score between the groups of patients and the control group ( P < 0.001). Conclusions: Results of conducted study indicate that SFI prevalence has not changed in the previous period. However, increase of Candida ‐SFI prevalence, especially Candida onychomycosis, was established.